Where eagles fly and the language of birds - Britton, Tony; Jarvis, Martin; Tomkins, John Pattison (Kuala Lumpur : Vision Four Home Video, 1994)
The two films explore the life of the elusive golden eagle and the complex language of birds
part 1. Where eagles fly (47 min.) - part 2. The language of birds (26 min.)
Title from container
Narrated by Tony Britton ; The language of birds is narrated by Martin Jarvis
Keywords: Eagles; Birds -- Vocalization